1998
DOI: 10.1136/bmj.317.7167.1181
|View full text |Cite
|
Sign up to set email alerts
|

Content and quality of 2000 controlled trials in schizophrenia over 50 years

Abstract: Objective To provide a comprehensive survey of the content and quality of intervention studies relevant to the treatment of schizophrenia. Design Data were extracted from 2000 trials on the Cochrane Schizophrenia Group's register. Main outcome measures Type and date of publication, country of origin, language, size of study, treatment setting, participant group, interventions, outcomes, and quality of study. Results Hospital based drug trials undertaken in the United States were dominant in the sample (54%). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
220
1
16

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(246 citation statements)
references
References 14 publications
9
220
1
16
Order By: Relevance
“…For example, a study of over 2000 trials in schizophrenia found that the mean sample size was about 60 (Thornley & Adams, 1998). And although Johnson (1998) from a search of the four leading psychiatric journals from 1956 thorough to 1996 found that the number of patients per treatment group in psychiatric trials was indeed rising over the four decades, the increase, from 17 to 25 over 40 years, was hardly impressive!…”
Section: Bigger Psychiatric Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of over 2000 trials in schizophrenia found that the mean sample size was about 60 (Thornley & Adams, 1998). And although Johnson (1998) from a search of the four leading psychiatric journals from 1956 thorough to 1996 found that the number of patients per treatment group in psychiatric trials was indeed rising over the four decades, the increase, from 17 to 25 over 40 years, was hardly impressive!…”
Section: Bigger Psychiatric Trialsmentioning
confidence: 99%
“…Psychiatrists also use far too many rating scales to measure far too many things in their trials, increasing the chances of false positive findings (as the Oxford, UK, group of trialists note, "many trials would be of much greater scientific value if they collected 10 times less data on 10 times more patients"). An analysis of trials on the Cochrane Schizophrenia Database found that over 640 different rating scales had been employed (Thornley & Adams, 1998: Gilbody et al, 2002. The use of a large number of outcome measures is driven by the fear of missing something that might be "clinically significant" even if that 'something' was not the primary reason for carrying out the study.…”
Section: Simpler Psychiatric Trialsmentioning
confidence: 99%
“…Despite several decades of educational efforts, RCTs still are not being reported adequately, [3][4][5][6]. For example, a review, [5] of 122 recently published RCTs that evaluated the effectiveness of selective serotonin reuptake inhibitors (SSRI) as first-line management strategy for depression found that only one (0.8%) paper described randomization adequately.…”
Section: Introductionmentioning
confidence: 99%
“…It is probably true to say that trials in mental health need to be much larger than they currently are (Hotopf et al, 1997;Thornley & Adams, 1998).…”
Section: Providing Evidence For Clinical Decision Making: the Emergenmentioning
confidence: 99%